HUBUNGAN PERILAKU PETUGAS KESEHATAN DAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA IBU PREOPERASI SEKSIO SESARIA - Elpriska; Romauli E.G.Siallagan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Childbirth not only involves physiological conditions but also involves psychological. Every delivery and delivery method both normal delivery and surgery (cesarean section) gives different experiences to maternity mothers so that in some mothers it can cause stress, fear or anxiety. Anxiety is a feeling of anxiety, worry or discomfort as if something happened that is perceived as a threat followed by certain physiological reactions such as. This study aimed to identify how the behavior of health workers and family support relates to anxiety levels in preoperative cesarean section mothers using descriptive correlation. The sample was 21 respondents at RSU Melati Perbaungan Medan. The sampling technique uses accidental sampling, which is the taking of respondents who happen to be present or available. The instrument was a questionnaire on the behavior of health workers, family support and anxiety levels in preoperative mothers of cesarean sections. The results showed a relationship between the behavior of health workers and family support with anxiety levels in preoperative cesarean section mothers where p < 0.05 and the relationship was strong, this was indicated by the value of r = 0.650. It can be concluded that the behavior shown by health workers and also support from family is very helpful to reduce anxiety in preoperative cesarean section mothers. For this reason, it is hoped that the RSU Melati Perbaungan will improve the quality of services, especially services for preoperative cesarean section mothers so that mothers get support from health workers. And health workers are expected to continue to improve the behavior of officers to increase the confidence of preoperative mothers.